Preparation of activated carbon by chemical activation and its in vitro adsorption efficacy tests for paraquat - Rahman, Md. Mokhlesur; Awang, Mohamed; Shajahan, Mohosina; Yunus, Kamaruzzaman; Miskon, Fuad; Karim, Md Rezaul (Kaerntner Botanikzentrum, Klagenfurt, Austria, 2014)
The effects of different activation temperature on the pore size and surface morphology of activated carbon produced by H3PO4 (30%) chemical activation were studied in this paper. Well developed pore size and highest surface area observed on activated carbon at 6000C were determined by Scanning Electron Microscope and Brunauer, Emmett and Teller (BET) method. The highest BET surface area was 1491 m2g-1 observed with sample HEAC-2 (highly efficient activated carbon -2). The adsorption efficacy of activated carbon for paraquat was also investigated and compared with commercially available activated carbon. The study shows that the amount of paraquat adsorbed was 3.62 mgL-1 for produced activated carbon and 3.42mg L-1 for commercially available activated carbon. The adsorbing capacity of activated carbon (produced and commercially available) for paraquat increased when it was suspended in NaCl (0.9%) solution. In the presence of NaCl solution, the amount of paraquat adsorbed increased from 3.62mg L-1 to 4.68mg L-1 for produced activated carbon and 3.42 mg L-1 to 4.18mg L-1 for commercially available activated carbon.